APPLICATION OF THE GENETTEAN THEORY OF THE NARRATIVE DISCOURSE ON THREE WEST AFRICAN AUTOBIOGRAPHIES - Odoi, D. A. (UDS International Journal of Development, 2016)
This paper focuses on West African autobiographies classified by Odoi (2010). He identifies four main sub groups of the autobiography namely: the factual autobiography, the fictionalised autobiography, the literary autobiography and the autobiographical fiction as present in many ways the works of practising writers in the West African sub Region. The last three types of autobiographies named above are glossed as having enough information and literary value to merit an analysis using the Genettean model. Genetteâ€™sÂ macrotextual demarcations of Time, Mood and Voice and their subcategories are used to show the differences between theseÂ three identified autobiographies. The paper also shows the three works on a continuum from the most factual to the most novelistic. Key words: Autobiography, Analepsis, Prolepsis ,Time, Mood, Voice, Diegesis